KEEPING FAITH WITH LIFE: MOTHER EARTH IN POPULAR RELIGIOUS TRADITIONS - Scott, David C (Journal of Dharma, 1993)
There is in our time an unprecedented explosion of interest in all facets of the genre religious tradition commonly termed "popular" or,' '{folk" . 1 Analyses of the complex reasons for this cmcern are outside the scope of our present task, but a few tentative observations may be proffered. Every society exhibits divisions and segmentations based on the classification of its members and their activities, functions, and relationships, such as, gender, work, knowledge, and so on. However, it was long a universally common assumption that the meaning of any institution within the society, or the meaning of the society as a whole, was the privileged province of the upper, or elite, levels of the society. Indeed, the idea that social meaning could be gained from any other level, especially, the lower levels of social structure, is a relatively new notion. The setting forth of the notion that a positive and necessary knowledge of society could be gained from its lower levels defined this strata as a locus of interpretation, meaning and value.